2010
DOI: 10.1007/s00784-009-0368-z
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between obesity, oral health and life-style factors among Turkish school children

Abstract: Obesity, dental caries and periodontal diseases are among major public health concerns which may affect children's growth and development. This study seeks any clustering between obesity, oral health and life-style factors among school children in Istanbul, Turkey. A cross-sectional study of children, 10- to 12-year-olds, from a public and a private school was undertaken with questionnaires for children and their mothers and child oral health data, in Istanbul (n = 611). DMFS (number of decayed, missing and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 43 publications
3
39
0
2
Order By: Relevance
“…Previous research developed in Turkey [29] showed that children from public schools had lower average BMI than children from private schools.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous research developed in Turkey [29] showed that children from public schools had lower average BMI than children from private schools.…”
Section: Discussionmentioning
confidence: 89%
“…Another study that examined the relationship between BMI and dental caries also found no association between these variables [29], although its sample included both genders and different age group (10-12 years). However, a study conducted in Saudi Arabia [35] found partial positive correlation between BMI and DMFT analyzing men and women aged 18 years or older.…”
Section: Discussionmentioning
confidence: 96%
“…9,10 The classifi cation of BMI showed no uniformity. Nine studies used the International Obesity Task Force (IOTF) for age and sex and seven assessed BMI through percentiles developed in the United States to determine the population's standard weight (Center for Disease Control and Prevention -CDC 2000).…”
Section: Resultsmentioning
confidence: 99%
“…5,[8][9][10]15,19,[22][23][24]27,29,33,36,40,41 Eight studies included adjustments for age and sex, 6,19,23,27,29,33,36,41 two only for sex, 15,22 and fi ve for consumption of any type of food, such as soft drinks, 10,24 fruits or snacks between meals, 10 "fast food", 10 and milk, 9 as well as daily sugar consumption 19 and "snack" consumption more than three times a day. 29 Among the 28 articles, 13 were considered to have good scientifi c evidence according to the criteria of Downs & Black.…”
Section: Resultsmentioning
confidence: 99%
“…Çalışmalardan bazıları pozitif ilişki tespit ederken (33-37), bazıları negatif ilişki tespit etmiştir (38)(39)(40)(41)(42). Bir kısım çalışma ise herhangi bir ilişki bulamamıştır (43)(44)(45)(46)(47).…”
Section: Obezite çüRük İlişkisiunclassified